Face paulista da TV digital: reflexão sobre a multiprogramação na TV cultura - Cardoso, Vivianne Lindsay [UNESP]; Carvalho, Juliano Maurício de [UNESP] (My University, 2011)
The implantation procedure of the multiprogramming for TV Cultura, a station under the responsibility of the Fundação Padre Anchieta,from the regulation of digital television in Brazil, through the Sistema Brasileiro de Televisão Digital Terrestre (SBTVD-T), involves the creation and implantation of multiprogramming channels of the station, the Univesp TV and the Multicultura channels, which are functioning through means of a special authorization in scientific and experimental character. Analyzed from the Communication Politics Economy point of view, this research contributes to the reflexion about the multiprogramming which may create alternatives to new options in this country programming and content.

El proceso de implantación de la multiprogramación por la TV Cultura, estación bajo responsabilidad de la Fundación Padre Anchieta, partiendo de la regulación de la televisión digital en Brasil, por medio de lo Sistema Brasileño de Televisión Digital Terrestre (SBTVD-T), envuelve la creación y implantación de los canales de multiprogramación de la estación, el Univesp TV y el Multicultura, que están en funcionamiento por medio de autorización especial en carácter científico y experimental. Analizando de la visión de Economía Política de la Comunicación, esta pesquisa contribuí con la reflexión sobre la multiprogramación que puede crear alternativas para nuevas opciones de programación y contenido en la televisión del país

O processo de implantação da multiprogramação pela TV Cultura, emissora sob responsabilidade da Fundação Padre Anchieta, a partir da regulação da televisão digital no Brasil, por meio do Sistema Brasileiro de Televisão Digital Terrestre (SBTVD-T), envolve a criação e implantação dos canais de multiprogramação da emissora, o Univesp TV e o Multicultura, que estão em funcionamento por meio de autorização especial em caráter científico e experimental. Analisado a partir da visão da Economia Política da Comunicação, esta pesquisa contribui com a reflexão sobre a multiprogramação que pode criar alternativas para novas opções de programação e conteúdo na televisão do País.
Digital TV paulista face: reflections on culture multiprogramming on TV
Keywords: Multiprogramming; Public television; Communication politics; Multiprogramación; Televisión publica; Políticas de comunicación; Multiprogramação; Televisão pública; Políticas de comunicação